Transparency as a democratic control in citizen councils: The case of the municipality of Leon, Guanajuato, 2009-2012 - José de Jesús Godínez-Terrones (Íconos)
In this research project transparency is analyzed as a form of democratic control in the citizen councils of the municipality of Leon, Guanajuato during the municipal administration of 2009-2012. Through the information available on the municipal portal this paper analyzes if the citizen participation in these councils is transparent in terms of its regulations and performance. From 1989 until 2012 the National Action Party (PAN) governed the municipality. During these 23 years it generated and consolidated the regulations and operations of the citizen councils as the expression of citizen participation of the political party that governed the municipality. This research is quantitative and descriptive and uses the samples of the regulations and proceedings that appear in the portal of transparency of the municipality of Leon, Guanajuato. The findings indicate that there are two types of citizen councils: governing and advising. Out of a total of 29 councils, only 12 publish their minutes and there is no sanction for this behavior. Citizen participation due to the institutional governmental design is presented more as a simulation than a condition for accountability and democratic control of government actions.